2016
DOI: 10.1115/1.4034522
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Viscous Disk Pump: Performance Variations From Non-Newtonian Elastic Turbulence

Abstract: Within the present investigation, a miniature viscous disk pump (VDP) is utilized to characterize and quantify non-Newtonian fluid elastic turbulence effects, relative to Newtonian flow behavior. Such deviations from Newtonian behavior are induced by adding polyacrylamide to purified water. The VDP consists of a 10.16 mm diameter disk that rotates above a C-shaped channel with inner and outer radii of 1.19 mm and 2.38 mm, respectively. A channel depth of 230 μm is employed. Fluid inlet and outlet ports are loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Due to the discrepancy of polymer relaxation time, chain length and molecular weight, different polymers [26,30] induced different onset values of elastic instability/turbulence, leading to various mixing performance. Flow in serpentine channels [24,[31][32][33][34] , porous media [35,36] and self-designed channel [37][38][39] has been recently studied and a consecutive curvilinear streamline is regarded as a necessary condition to trigger elastic instabilities. All these studies showed that the elastic turbulence could indeed benefit the mixing performance.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the discrepancy of polymer relaxation time, chain length and molecular weight, different polymers [26,30] induced different onset values of elastic instability/turbulence, leading to various mixing performance. Flow in serpentine channels [24,[31][32][33][34] , porous media [35,36] and self-designed channel [37][38][39] has been recently studied and a consecutive curvilinear streamline is regarded as a necessary condition to trigger elastic instabilities. All these studies showed that the elastic turbulence could indeed benefit the mixing performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unlike the swirling flow, a steady secondary flow was observed in such a geometry before the onset of elastic turbulence [35]. Besides these standard geometries related to rheometer, elastic turbulence was also triggered in any other geometries, such as porous media [19-21, 36, 37], cross-slot channel [38] and viscous disk pump [39,40]. From these curvilinear geometries, the curvature of the geometry was regarded as an essential condition to induce elastic turbulence or instability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was carried out to change the induced slip by using different levels of surface roughness on the rotating disc [113]. The micro viscous disc pump (VDP) was used to characterize and quantify the elastic turbulence effect of non-Newtonian fluid relative to Newtonian fluid behavior [114,115], as shown in Figure 7.…”
Section: Physical Model With Extended Applicationmentioning
confidence: 99%